A Simple and Safe Spectrophotometric Method for Iodide Determination - Sulistyarti, Hermin; Atikah,; Fardiyah, Qonitah; Febriyanti, Sita; Asdauna, (UI Scholars Hub, 2015)
In order to practice green chemistry, a simple and safe spectrophotometric method for iodide determination has been successfully developed based on the formation of a blue starch-iodine complex. Iodide was oxidized to form iodine prior to the addition of a starch solution, and the blue starch-iodine complex was directly detected spectrophoto-metrically at a wavelength of 615 nm. The chemical parameters, such as type, reaction time, as well as concentration of oxidizing agents and solution pH were optimized with respect to sensitivity and analysis time. The method showed optimum results under iodate oxidant with a mol ratio of IO3-:I- =1:3, reaction time of 5 minutes, and solution pH of 5. Under these optimum conditions, the method showed linierity measurements from 5-40 mg/L iodide with a correlation (R2) of 0.9889. This technique offers a simple, safe, accurate, and relatively fast method for iodide determination, which is prospective for monitoring iodide samples.